Pengembangan Produk Selai Lembaran Berbasis Pepaya Sebagai Produk Unggulan UMKM Dapur Ibu Yanti Bandar Lampung - Wahyuningtyas, Amalia; Ulfa, Masayu Nur; Talitha, Zada Agna; M. Rizky Ramanda; Adawiyah, Mala Minati; Hutasoit, Tania Jessika; Inayah, Rahmadya; Titienchu Srihan Drewtry Naibaho; Christian, Dhea (Forum Kerjasama Pendidikan Tinggi, 2024)
Dapur Ibu Yanti is one of the micro, small and medium enterprises (MSMEs) located in Segalaminder Village, Bandar Lampung. Currently, the products produced by Dapur Ibu Yanti are still limited, only donuts and kue lapis which is flour based are produced every day. Innovation must be carried out to make consumers more interested in their products, especially by utilizing local raw materials such as papaya. Papaya fruit has the potential to be used as an innovative food product that can be developed into sheet jam as a superior product in Dapur Ibu Yanti. Sheet jam is jam that is thin, shiny, has a soft, compact texture, is plastic and not sticky and has a natural fruit taste. The team carried out community service by making sheet jam from papaya fruit and then the results of the innovation in developing papaya sheet jam were taught to culinary practitioners, namely in Dapur Ibu Yanti. The aim of this activity was to process papaya fruit into a featured product known as sheet jam. The method used was a field survey, interviews with key culinary actors, and continued with direct training by making papaya sheet jam. The output of this service was papaya sheet jam that could be the featured product which can increase economic value and become an innovative product in Dapur Ibu Yanti.